2006
DOI: 10.1002/eat.20351
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among attachment styles, personality characteristics, and disordered eating

Abstract: These results suggest that relationships between attachment style and disordered eating are indirect, in that neuroticism fully mediates associations between insecure-resistant attachment and disordered eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…The NEO-PI-R has proven to exhibit good convergent validity between community and psychiatric samples (Bagby et al 1999). In addition, it has demonstrated strong internal consistency (0.86-0.92) and testretest reliability (0.79-0.83) (Costa and McCrae 1992;Eggert et al 2007;Santor et al 1997). In the study reported here, internal consistencies of all subscales ranged between Cronbach's a = 0.51 and a = 0.92.…”
Section: Neo-personality Inventory-revised (Neo-pi-r)mentioning
confidence: 99%
“…The NEO-PI-R has proven to exhibit good convergent validity between community and psychiatric samples (Bagby et al 1999). In addition, it has demonstrated strong internal consistency (0.86-0.92) and testretest reliability (0.79-0.83) (Costa and McCrae 1992;Eggert et al 2007;Santor et al 1997). In the study reported here, internal consistencies of all subscales ranged between Cronbach's a = 0.51 and a = 0.92.…”
Section: Neo-personality Inventory-revised (Neo-pi-r)mentioning
confidence: 99%
“…In a cross-sectional study with a clinical sample, Fossati et al (2005) concluded that impulsive and aggressive traits mediated the relationship between adult attachment patterns and BPD features. In addition, Eggert, Levendosky, and Klump (2007) recently reported that trait neuroticism and extraversion mediated the relationship between insecure-resistant adult attachment (analogous to preoccupied attachment) and disordered eating. Even though causality and primacy cannot be inferred from cross-sectional data, these results lend support to a model in which the relationship between attachment and BPD might be mediated by personality traits.…”
mentioning
confidence: 99%
“…Eggert and collaborators showed that in healthy population attachment insecurity and body dissatisfaction could be both explained by considering personality traits [29]. Abbate-Daga et al explored a clinical group and came to different conclusions.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%